Trend of bed load material and bed load transport in Sungai Kenau for year 2013 until 2020. Issue 1 (February 2021) - Nadiatul Adilah, A A G; Lukman, M
Abstract: A study was carried out to determine the trend of bed load material characteristic and bed load transport rate in Sungai Kenau at Sungai Lembing, Kuantan, Pahang between year 2013 until 2020. Sediment is a material that can be moved and deposited to the new location through the river. This study will be focusing in bed load transport as it is the key component to determine the sediment transport rate in the river. Two sampling station have been chosen to measure the bed load transport in year 2013 until to 2020. Schocklitsh and Duboys equation was used to predict sediment transport load and it was compared with measured sample from Helly-Smith equipment. The collected sample was analysed to determine the trend of bed load material and bed load transport in Sungai Kenau for year 2013 until 2020. According to Duboys calculation the highest bed load transport rate is Sample 1 with 0.013220 lb/sec and the lowest is on Sample 5 with 0.002310 lb/sec both of the samples are taken on the same station but on the different day. Meanwhile according to Schocklitsh calculation the highest bed load transport rate is Sample 7 with 3.79374 lb/sec and the lowest is on Sample 5 with 1.98018 lb/sec both of the samples also taken on the same station but on the different day. It can be sure that the higher flow rate of the river the higher bed load transport rate. It can be obtain that according to Wentworth Scale the median grain size in Sungai Kenau were between 0.68 mm to 2.6 mm where the bed material can be classified as coarse sand to the very fine gravel.